Enhancing Student Comprehension of Heat and Expansion with an Animated Direct Learning Model - Mariati Mariati; Zakiah Zakiah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study investigates the effectiveness of the Direct Learning Model (DLM) integrated with animated media in improving student learning outcomes on the topic of heat and expansion in junior high school. Initial observations at SMP Negeri 3 Muara Tiga revealed that conventional DLM was predominantly teacher-centred, lacked engaging media, and resulted in student boredom and low retention. To address this issue, the study employed animated media, which has the advantage of concretising abstract scientific concepts and enhancing student motivation. This research utilised a mixed-method approach combining qualitative and quantitative analysis. The design applied was a one-group pre-test and post-test model. The sample consisted of seventh-grade students selected through cluster random sampling. Data were collected through multiple-choice tests and interviews. The pre-test and post-test assessed cognitive outcomes, while interviews explored students’ difficulties in understanding physics concepts using animated media. The results showed a significant improvement in learning outcomes, with the average pre-test score of 60.1 increasing to 81 in the post-test. The N-Gain score was 0.5, indicating a moderate improvement. Statistical analysis also confirmed a significant correlation between the use of animated media and enhanced learning outcomes. In conclusion, the implementation of the Direct Learning Model using animated media positively affects student learning outcomes in science, especially on abstract topics like heat and expansion. However, some students experienced challenges, particularly in connecting animation with scientific concepts, indicating the need for scaffolding in media integration.